Application of The Circ Learning Model to Improve Student's Reading and Writing Skills in The Yellow Kitab Subject - Mochammad Syafiuddin Shobirin; Maya Wafiroh (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
The application of the Circ (Cooperative Integrated Reading and Composition) learning model to improve students' reading and writing skills in the yellow kitab subject at Madrasah Al-i'dadiyyah Bahrul Ulum is said to be successful if the activities that are part of the madrasa program can be carried out properly and in accordance with expectations . Based on this, previously at Madrasah Aliyah Al-I'dadiyyah using the sorogan or listening method, so that students' reading and writing skills are still low. In an effort to improve reading and writing skills in the yellow kitab subjects, the teacher applies a cooperative model. This study uses qualitative research. Based on the results of the research that in an effort to apply the Circ learning model to improve reading and writing skills in the yellow kitab subjects, students are more active in learning the yellow book and helping students who are weak in understanding the yellow kitab due to the method used. been around all along. This can be proven by the majority of students who have achieved the KKM score of 80.0 with the Circ learning model. The role of teachers and students is very important in order to become graduates who are useful in the community and in accordance with the vision and mission of the madrasah.